2021
DOI: 10.3390/molecules26216375
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Hydrogen Gas Attenuates Oxidative Stress in Airway Epithelial Cells

Abstract: Oxidative stress plays a crucial role in the development of airway diseases. Recently, hydrogen (H2) gas has been explored for its antioxidant properties. This study investigated the role of H2 gas in oxidative stress-induced alveolar and bronchial airway injury, where A549 and NCI-H292 cells were stimulated with hydrogen peroxide (H2O2) and lipopolysaccharide (LPS) in vitro. Results show that time-dependent administration of 2% H2 gas recovered the cells from oxidative stress. Various indicators including rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Hydrogen has significant therapeutic effects on the dysfunction of organs such as intestine, kidney, liver, lung, myocardium and brain. Not only that, it also has definite therapeutic effect on type 2 diabetes, multiple organ injury, sepsis, atherosclerosis, tumor and many other diseases [ 19 , 20 , 21 , 22 , 23 , 24 ]. At present, we know that hydrogen is insoluble in water.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen has significant therapeutic effects on the dysfunction of organs such as intestine, kidney, liver, lung, myocardium and brain. Not only that, it also has definite therapeutic effect on type 2 diabetes, multiple organ injury, sepsis, atherosclerosis, tumor and many other diseases [ 19 , 20 , 21 , 22 , 23 , 24 ]. At present, we know that hydrogen is insoluble in water.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits ERK through competition with ATP (Type I ATP inhibitor) [ 38 , 39 ]. FR180204 has been shown to have an antiproliferative effect in different cancer cell lines, including adrenocortical, mesothelioma, prostate, pancreatic, and colorectal cell lines [ 40 , 41 ]. Similarly, XAV-939 has been shown to target the Wnt/B-catenin signaling pathway by inhibiting tankyrases 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MARW enhanced antioxidant activities against HG-induced OS, which supports our ROS and NO results. Antioxidant enzymes, such as GPx and CAT, can help cells to recover from the effects of OS [32][33][34]. These antioxidants are well known for their involvement in lowering OS effectors such as ROS and NO levels in HK-2 cell lines [32,35].…”
Section: Discussionmentioning
confidence: 99%
“…p-p38 and p-JNK are downstream proteins of the MAPK pathway and play important roles in early OS and cellular responses [43,44]. Previously published studies have confirmed that, with blocking, the MAPK signaling pathway can aid in the survival of cells in a redox imbalance state [34,45,46]. However, it has been explained that ARW increases endogenous antioxidants that help to protect cells from OS [32].…”
Section: Discussionmentioning
confidence: 99%